Ecological urban design: approaches to waterfront revetment - Galkin, Dmitry V. (Вестник Томского государственного университета. Культурология и искусствоведение)
Authors present detailed analysis of ecological urban design applied to waterfront revetment. Modern claim of ecological values makes traditional methods of waterfront construction insufficient and inconsistent. With the growth of ecological awareness and values, people pay more and more attention to the different aspects of urban design including construction of urban waterfront. The structure and function of urban waterfront reflects ecological values and culture of cities as the driving force of economy and industry become more and more complex. Revetment considered as boundary line between water area and land area, which is the forefront of land area relative to water. The design of the revete determines whether the waterfront can become an important factor to shape city culture, public life and attract tourists. This paper discusses the meaning and importance of ecological revetment, and the different ecological revetment chosen by different river types according to local conditions. Traditional revetment design criticized since it often ignores the ecological relationship between water body, land and animals and plants, and hinders the ecological circulation system of waterways. Another serious problem considered is lack of inheritance of local historical and cultural context as well as lack of consideration of people's mental and physical needs. Authors advocate new design approach with focus on ecological values in revetment design which based on the balance the urban water environment, balance between land and water ecosystems, enhancing the self-purification effect of water body and focus on social/cultural attractiveness of revetment. Authors analyze different methods of urban ecological waterfront design: natural prototype revetment that mainly adopts plant protection embankment; natural revetment that not only planting vegetation, but also using natural stone and wood to protect the bottom, in order to enhance the flood resistance of the embankment; artificial natural revetment on the basis of natural revetment, reinforced concrete and other materials are used to strengthen flood resistance. Authors also summarize 8 common ecological revetment design methods based on international practices: natural gentle slope revetment, ecological engineering revetment, block type natural revetment; grassy slope and step revetment; waterfront wharves and barges; boardwalk and revetment; retreating from the bench revetment; ecological vertical revetment. Introducing author's own original sketches and plans for urban ecological waterfront design, they give common principles of waterfront landscape design such as 1) natural environment priority principle guided by landscape ecology; 2) strong links with urban planning and urban design; 3) large-scale space utilization determined by functional requirements (waterfront landscape belt usually uses a larger design scale to meet the entertainment needs of residents and tourists); 4) cultural adaptation according to local conditions (landscape design should start from the urban culture and create a landscape space with local characteristics); 5) emphasize the accessibility of hydrophilic spaces. These common principles are also the trend of waterfront landscape design. In the application of self-purification water system in waterfront landscape design, by following these design principles, the design scheme can achieve the effect of water self-purification, and can also construct It is a landscape space with strong tourist attraction and beautiful environment with local natural and cultural characteristics.